Komparasi Perma Nomor 7 Tahun 2022 dalam Rbg (Tata Cara Persidangan) Dan Panggilan Surat Tercatat KMA Studi Kasus Pengadilan Agama Tanjungpandan Kelas 1B - Huda, M. Nurul; Prayuda, Hidayatullah; Anwar, Reski; Mukhafidhoh, Lucky; Rismawanti, Rismawanti (ISLAMITSCH FAMILIERECHT JOURNAL, 2025)
This research aims to analyze and compare PERMA No. 7 of 2022 with provisions in the Burgerlijk Rechtsvordering (RBG) Regulations regarding trial procedures and the use of registered letters based on the provisions of the Supreme Court (KMA). The approach used is normative juridical, based on applicable laws and regulations. Apart from that, this research also uses an empirical approach through interviews with religious court employees to gain practical understanding regarding the implementation of these regulations. The research results are expected to provide differences between PERMA No. 7 of 2022 and RBG, as well as the registered letter summons process at the Tanjungpandan Religious Court. Keywords: Perma number 7 of 2022, Registered Letter Summons. Keywords: PERMA No. 7 of 2022, Burgerlijk Rechtsvordering (RBG), Registered Letter Summons.